2016
DOI: 10.22159/ijpps.2016v8i12.13564
|View full text |Cite
|
Sign up to set email alerts
|

Using Essential Oils to Combat the Threat of Multi-Drug Resistant Bacteria, Pseudomonas Aeruginosa

Abstract: Objective: The development of antibiotics was a revolutionary scientific discovery and medical advancement that greatly extended the life expectancy of mankind. Through less than 100 y of using antibiotics to treat infectious bacteria, some of these highly adaptive organisms have developed resistance to the drugs. The healthcare field is greatly concerned with the threat of many common infections that have been considered treatable for decades, regaining its ability to be severely fatal; thus, making alternati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 8 publications
1
1
0
Order By: Relevance
“…Our results are in accordance with a previous study showing that the inhibitory halos produced by the EOs of OR, TY, and CL were larger than those produced by ciprofloxacin [33] and cefuroxime [11]. Grullon et al [34] tested EOs from cassia, cinnamon bark, cinnamaldehyde, and methylglyoxal using the disc diffusion method. The study showed that cinnamaldehyde and methylglyoxal were as effective or better in inhibiting the growth of P. aeruginosa compared to standard aminoglycoside antibiotics.…”
Section: Discussionsupporting
confidence: 93%
“…Our results are in accordance with a previous study showing that the inhibitory halos produced by the EOs of OR, TY, and CL were larger than those produced by ciprofloxacin [33] and cefuroxime [11]. Grullon et al [34] tested EOs from cassia, cinnamon bark, cinnamaldehyde, and methylglyoxal using the disc diffusion method. The study showed that cinnamaldehyde and methylglyoxal were as effective or better in inhibiting the growth of P. aeruginosa compared to standard aminoglycoside antibiotics.…”
Section: Discussionsupporting
confidence: 93%
“…Various studies have proved that TC shows antimicrobial activity against various bacterial strains such as Listeria monocytogenes, Staphylococcus aureus, E. coli, and Salmonella species [7][8][9]. Cinnamaldehyde was found comparable or better in restricting the growth of Pseudomonas aeruginosa as compared to the standard aminoglycoside antibiotics [10]. However, the use of TC is limited due to the factors such as insolubility in water, the high volatility, low bioavailability, and their role in causing skin irritation [11].…”
Section: Introductionmentioning
confidence: 99%